Application and fabrication aspects of sub-micrometer-sized Josephson junctions - Oelsner, G.; Hübner, U.; Anders, S.; Il`ichev, E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
We present two possible methods for the fabrication of sub-micron sized Josephson junctions, namely the shadow-evaporation technique and the cross-type technology. Their importance for the field of modern super-conducting technology is discussed. As examples we present measurement results of a two-qubit sample and a prototype of a microwave detector fabricated each by one of the described methods. We review potential applications of superconducting quantum circuits based on the developed methods.